Specificity of Furanoside–Protein Recognition through Antibody Engineering and Molecular Modeling - Lak, Parnian (Chemistry, 2014)
Recognition of furanosides (five-membered ring sugars) by proteins plays important roles in host–pathogen interactions. In comparison to their six-membered ring counterparts (pyranosides), detailed studies of the molecular motifs involved in the recognition of furanosides by proteins are scarce. Here the first in-depth molecular characterization of a furanoside–protein interaction system, between an antibody (CS-35) and cell wall polysaccharides of mycobacteria, including the organism responsible for tuberculosis is reported. The approach was centered on the generation of the single chain variable fragment of CS-35 and a rational library of its mutants. Investigating the interaction from various aspects revealed the structural motifs that govern the interaction, as well as the relative contribution of molecular forces involved in the recognition. The specificity of the recognition was shown to originate mainly from multiple CH–π interactions and, to a lesser degree, hydrogen bonds formed in critical distances and geometries.